The Application of Fair Value in Commercial Banking and its Relationship to Transparency Financial Statements - Evidence from Iraq - Dawad, Mohammad Salman; Khlaif, Murtadha Hasan; Wahhab, Asaad Mohammed Ali (Technium Social Sciences Journal, 2022)
The research aims to demonstrate the impact of applying this measurement in improving the transparency of financial reporting and its application in Iraqi companies. A high level of transparency in the financial statements has been shown. It has been concluded that the level of transparency of the financial statements when choosing the fair value measurement is higher than the level of transparency when choosing the historical cost measurement, which helps in comparing the financial statements of the different economic units, and that the basis of comparison between it and the measurement based on Historical cost is to achieve the required amount of appropriateness characteristic and honest representation.